Happiness of Working Mothers Through Family Life Stages - Tina Afiatin; Ilma Putri Istianda; Annisa Yuliarahma Wintoro (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2016)
The happiness of working mothers greatly affects the well-being of family. The objective of this study is to examine the happiness of working mothers in the stages of family life cycle of having: (a) the first child aged 0-35 month old; (b) the first child at pre-school age; (c) the first child at school age; (d) the first child at adolescent age; and (e) the first child who has married, by controlling the effect of work-family balance. Participants were 526 working mothers with children and a working husband. Data were collected using the Happiness Scale and the Work-Family Balance Scale. Data were analyzed using ANCOVA. The results showed that there were differences in the happiness of working mothers at different stages of family life cycles (F = 2.55; p < .05). Working mothers with the first child at pre-school age had the highest level of happiness, whilst those with the married first child had the lowest level of happiness. The levels of working mothers’ happiness were mostly influenced by the level of work-family balance rather than family life cycle.